I have from a previous question these answers:
Fn+3 = Fn+2 + Fn+1 & Fn = Fn+2 - Fn+1
I have to use these answers to show that:
Fn+3 + Fn = 2Fn+2 & Fn+3 - Fn = 2Fn+1 for n = 0, 1, 2,...
I'm not sure how to do this although I understand that the second set of statements are true.
Any help would be really appreciated :)
You want to show that:
Originally Posted by bigroo
You begin by using the recurrence for the Fibonacci numbers on , then group terms if you try that and have further difficulties post what you have done and tell us what difficulties you are having with it.